2015
DOI: 10.1016/j.biopsych.2015.01.015
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Pharmacologic Inhibition of 5-Lipoxygenase Improves Memory, Rescues Synaptic Dysfunction, and Ameliorates Tau Pathology in a Transgenic Model of Tauopathy

Abstract: Background The 5-lipoxygenase (5LO) is a protein widely distributed in the central nervous system where modulates amyloidosis and memory impairments in transgenic mouse models of Alzheimer’s disease. However, no data are available as to whether 5LO is elevated in human tauopathy, or if it directly influences tau pathology in a relevant model of the disease. Methods We assayed 5LO levels in brain samples from tauopathy patients and transgenic tau mice, and evaluated the effect that 5LO pharmacological inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…Immunoblot analyses were performed as previously described15, 16. Briefly, proteins were extracted in enzyme immunoassay buffer containing 250 mmol/L Tris base, 750 mmol/L NaCl, 5% NP‐40, 25 mmol/L EDTA, 2.5% sodium deoxycholate, 0.5% sodium dodecyl sulfate, and an EDTA‐free protease and phosphatase inhibitors cocktail tablet (Roche Applied Science, Indianapolis, IN, USA), sonicated, centrifuged at 56,700 g for 45 min at 4°C, and supernatants used for immunoblot analysis, as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunoblot analyses were performed as previously described15, 16. Briefly, proteins were extracted in enzyme immunoassay buffer containing 250 mmol/L Tris base, 750 mmol/L NaCl, 5% NP‐40, 25 mmol/L EDTA, 2.5% sodium deoxycholate, 0.5% sodium dodecyl sulfate, and an EDTA‐free protease and phosphatase inhibitors cocktail tablet (Roche Applied Science, Indianapolis, IN, USA), sonicated, centrifuged at 56,700 g for 45 min at 4°C, and supernatants used for immunoblot analysis, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse brain homogenates were sequentially extracted first in RIPA buffer for the soluble and then in formic acid (FA) for the insoluble protein fraction as previously described15, 16. A β 1‐40 and A β 1‐42 levels were assayed by a sensitive sandwich ELISA kits (WAKO Chem., Richmond, VA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5LO enzymatic pathway, which upon activation produces potent inflammatory mediators, has recently emerged as a novel target in neurodegeneration (Chu & Praticò, 2011b; Joshi et al ., 2014). Importantly, our group has shown that steady‐state levels of 5LO are increased in brain cortices from subjects with a postmortem diagnosis of PSP and that pharmacological inhibition of its activity ameliorates tau pathology and behavioral deficits in the htau mice (Giannopoulos et al ., 2015b). To gather further support and confirm that 5LO is indeed an active player in the tauopathy phenotype, in the current study, we implemented a different mouse model of tauopathy, the P301S line, and a new and opposite experimental approach, 5LO gene over‐expression, which by stably increasing the levels and activity of this pathway in the CNS of these mice, should exacerbate their pathological phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that 5LO acts as an endogenous modulator of Aβ formation in vitro and in vivo by influencing the development of the AD‐like phenotype in transgenic mouse models of the disease (Firuzi et al ., 2008; Chu & Praticò, 2011a; Chu et al ., 2012a; Giannopoulos et al ., 2014). More recently, we reported that selective pharmacological inhibition of 5LO activity ameliorates tau neuropathology and behavioral impairments of htau mice, a transgenic mouse model expressing wild‐type human tau (Giannopoulos et al ., 2015b). …”
Section: Introductionmentioning
confidence: 99%